Indonesia's Struggle For Democratic Resilience: Issues and Institutional Reforms - Mi’rojul Huda; Mubarok Muharam; Mochamad Arif Affandi; Agus Satmoko Adi; Silkania Swarizona; Eko Satriya Hermawan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Indonesia's democracy, despite over two decades of progress since the fall of the New Order regime, has faced stagnation and democratic backsliding in recent years. Indicators from institutions such as the Economist Intelligence Unit (EIU), Freedom House, and Varieties of Democracy (V-Dem) consistently highlight a decline in democratic quality. Contributing factors include identity politics, declining electoral integrity, political dynasties, and weak institutional capacities, described as